Diagnosis and Correction of Hemostatic Disorders in Severe Brain Injury - Ye. A. Kameneva (Obŝaâ Reanimatologiâ, 2006)
A rapid diagnosis of hemostatic disorders in the acute period of severe brain injury was clinically tested by using the continuous automatic recording of resonance oscillations occurring with the formation, retraction, and lysis of a clot. Pathogenetic correction of hemostatic disorders was developed and clinically tested in severe brain injury, which was performed, by taking into account the severity of neurological symptoms. This made it possible to reduce the incidence of pulmonary complications and the rates of mortality.